Empirical constraints for the magnitude and composition of galactic winds - Zahid, H. Jabran (2014)
Galactic winds are a key physical mechanism for understanding galaxy formation and evolution, yet empirical and theoretical constraints for the character of winds are limited and discrepant. Recent empirical models find that local star-forming galaxies have a deficit of oxygen that scales with galaxy stellar mass. The oxygen deficit provides unique empirical constraints on the magnitude of mass loss, composition of outflowing material and metal reaccretion onto galaxies. We formulate the oxygen deficit constraints so they may be easily implemented into theoretical models of galaxy evolution. We parameterize an effective metal loading factor which combines the uncertainties of metal outflows and metal reaccretion into a single function of galaxy virial velocity. We determine the effective metal loading factor by forward-fitting the oxygen deficit. The effective metal loading factor we derive has important implications for the implementation of mass loss in models of galaxy evolution.